The Effect of Enterprise Risk Management and Intellectual Capital Disclosure on Firm Value - Wendy Salim Saputra; Yongki Saputra; Kartika Koswara; Stevani Wahyu Herawati; Laurensia Amelia Septi Anggita Sae (Dinasti International Journal of Education Management And Social Science, 2023)
The establishment of a company has a clear purpose. In carrying out business activities to achieve company goals, of course the company will face various risks. Risk can be said as the possible outcome of a process that does not meet expectations. ERM began to be recognized by the public after the Committee of Sponsoring Organization of The Treadway Commission (COSO) published it in 2004. ERM can be said to be a comprehensive and useful approach for managing overall corporate risk, reducing threat levels, and maximizing opportunities. Apart from enterprise risk management, intellectual capital is also an important non-financial information to be disclosed in a company's financial statements. Intellectual Capital is information and knowledge that can be applied to a job to create value in the company. The purpose of this study was to determine the effect of disclosure of enterprise risk management and intellectual capital on company value in LQ45 companies listed on the Indonesia Stock Exchange in the 2018-2020 period. The research method used in this research is hypothesis testing, namely to analyze the effect of enterprise risk management disclosures and company value intellectual capital. Based on the research conducted, it was found that enterprise risk management affects firm value in a negative direction, while intellectual capital has no effect on firm value.